Peran Quiet Cracking dalam Memediasi Burnout dan Job Insecurity Terhadap Turnover Intention: Studi pada Karyawan Retail Moderen - Widia Sapitri; Erna Listiana; Ilzar Daud; Rizky Fauzan; Arman Jaya (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
High turnover intention is a major challenge in the modern retail sector, characterized by high work demands and employee psychological stress. Although job insecurity and burnout have been widely studied as factors influencing employee turnover intention, the psychological mechanisms that bridge this relationship are still relatively limited, particularly in the context of the Indonesian retail industry. This study aims to analyze the influence of job insecurity and burnout on turnover intention, with quiet cracking as a mediating variable. The study used a quantitative approach with a causal associative design. Data were collected through an online questionnaire from 150 Indomaret employees in Ketapang Regency and analyzed using Structural Equation Modeling–Partial Least Squares (PLS-SEM). The results showed that job insecurity and burnout had a positive and significant effect on quiet cracking and turnover intention. Furthermore, quiet cracking was shown to partially mediate the relationship between job insecurity, burnout, and turnover intention. These findings suggest that employee turnover intention is formed through a gradual psychological process that begins with work pressure, progresses to disengagement, and finally gives rise to a tendency to leave the organization. This study contributes to the human resource management literature by positioning quiet cracking as a psychological mechanism that bridges the relationship between work stress and employee turnover intention in the context of the modern retail sector.